An implementation of the ADM for generalized one-dimensional Klein-Gordon equation - Kaya, D (Elsevier Science Inc, 2005)
In this study, a decomposition method for approximating the solution of the generalized one-dimensional Klein-Gordon equation is implemented. To illustrate the application of this method numerical results are derived by using the calculated components of the decomposition series. The obtained results are found to be in good agreement with the exact solution. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: the decomposition method; the generalized one-dimensional Klein-Gordan equation; traveling wave solution; solitary wave solution